Complete Genome Sequence and Characterization of Linezolid-Resistant Enterococcus faecalis Clinical Isolate KUB3006 Carrying a cfr(B)-Transposon on Its Chromosome and optrA-Plasmid - Kuroda, Makoto; Sekizuka, Tsuyoshi; Matsui, Hidehito; Suzuki, Katsunori; Seki, Hiroyuki; Saito, Mitsumasa; Hanaki, Hideaki (Frontiers in Microbiology, 2018)
Linezolid (LZD) has become one of the most important antimicrobial agents for infections caused by gram-positive bacteria, including those caused by Enterococcus species. LZD-resistant (LR) genetic features include mutations in 23S rRNA/ribosomal proteins, a plasmid-borne 23S rRNA methyltransferase gene cfr, and ribosomal protection genes (optrA and poxtA). Recently, a cfr gene variant, cfr(B), was identified in a Tn6218-like transposon (Tn) in a Clostridioides difficile isolate. Here, we isolated an LR Enterococcus faecalis clinical isolate, KUB3006, from a urine specimen of a patient with urinary tract infection during hospitalization in 2017. Comparative and whole-genome analyses were performed to characterize the genetic features and overall antimicrobial resistance genes in E. faecalis isolate KUB3006. Complete genome sequencing of KUB3006 revealed that it carried cfr(B) on a chromosomal Tn6218-like element. Surprisingly, this Tn6218-like element was almost (99%) identical to that of C. difficile Ox3196, which was isolated from a human in the UK in 2012, and to that of Enterococcus faecium 5_Efcm_HA-NL, which was isolated from a human in the Netherlands in 2012. An additional oxazolidinone and phenicol resistance gene, optrA, was also identified on a plasmid. KUB3006 is sequence type (ST) 729, suggesting that it is a minor ST that has not been reported previously and is unlikely to be a high-risk E. faecalis lineage. In summary, LR E. faecalis KUB3006 possesses a notable Tn6218-like-borne cfr(B) and a plasmid-borne optrA. This finding raises further concerns regarding the potential declining effectiveness of LZD treatment in the future.